Bilateral Ocular Ischaemic Syndrome due to Carotid Artery and Cardiovascular Disease: A Case Report: Poster Presentation - Case Report - Ophthalmologist - FIBRIAN, KARTIKA CINDY (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular ischemic syndrome (OIS) is a rare but potentially blinding and fatal condition caused by carotid artery disease or other systemic condition results in ocular hypoperfusion. Case Illustration : A 62-year-old male with sudden bilateral vision loss, swelling, redness and pain of both eye for 7 days. There were dilated conjunctival and episcleral vessels, visual acuity of the right eye was hand movement and 0.05 for left eye, intraocular pressure (IOP) was 33 mmHg in right eye and 37 mmHgfor left eye. Anterior segment evaluation revealed rubeosis iris, mild anterior chamber reaction, and temporal angle neovascularization on gonioscopy. Both direct and consensual light reflexes were sluggish. Fundus examination showed normal optic disc, minimal hemorrhages at mid-periphery, narrowed arterioles, and minimal cotton wool spot. Macular OCT demonstrated discrete hyperreflectivity of inner retinal layers. From Macular Angiography OCT, ETDRS Central vessel density were 11.2% and 17.6% for the right eye and left eye, respectively. In both eyes, paracentesisof anterior chamber, intravitreal and intracameral injections of anti-VEGF were performed. Brain Magnetic Resonance Angiography Imaging revealed moderate stenosis of both distal carotid artery circulation. Percutaneous Coronary Angiography showed extensive stenosis in coronary artery, with low Ejection Fraction. Discussion : For the cardiovascular management, a pacemaker was implanted. One week after procedure, BCVA were 1/60 and 0.15, and IOPs of 17 and 18 mmHg, for the right and left eye, respectively. The patient was scheduled to have laser retinal photocoagulation. Conclusion : Quick clinical diagnosis, targeted workup for systemic associations, and prompt treatment might preserve life and sight in OIS.